Recrystallization of Cu-30Zn brass during friction stir welding - N. Xu; L. Chen; R.N. Feng; Q.N. Song; Y.F. Bao (Journal of Materials Research and Technology, 2020)
The recrystallization process of Cu-30Zn brass during friction stir welding (FSW) was investigated. The microstructural evolution in the stirring period and the subsequent normal air-cooling period were separately studied by using stop-action technology, liquid nitrogen cooling, and subsequent heat treatment. During the stirring period, the initial large grains in the base material underwent serious shear deformation at elevated temperatures, resulting in the occurrence of dynamic recrystallization. The weld exhibited ultrafine grains with high dislocation density and a typical {111}<110> shear texture. The grain refinement mechanism was mainly attributed to discontinuous dynamic recrystallization, although several features of continuous dynamic recrystallization could also be found. In the subsequent normal air-cooling period, static restoration occurred and led to dislocation annihilation, selected grain growth, and appearance of annealing twins. The {111}<110> textural component partially changed into a {110}<001> Goss recrystallization texture. From these results, it was deduced that the brass experienced static restoration following dynamic recrystallization during FSW. The static restoration produced by the stirring remarkably influenced the microstructure. This study concluded that if the rapid cooling method is adopted during FSW, the static restoration process can be effectively restrained, and the microstructure of the joint can be significantly improved.